Племянник чародея - Льюис Клайв Стейплз (Хроники Нарнии, 2016)
Экземпляры: СБ (20160815) / Инвентарный номер: 52483 / Цена: 279.00 / Сис.шифр: И(англ)ср / Авт.знак: Л 91 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)